Evaluation of Seven Taro Cultivars [Colocasia esculenta (L.) Schot] for Yield and Corm Quality under Poultry Manure Fertilization in Anyigba, Kogi State, Nigeria (Applied Research and Innovation, 2024)
The study was conducted at the Prince Abubakar Audu University Research and Demonstration Farm, Anyigba, during the 2021 Cropping Season to evaluate seven taro cultivars for yield and corm quality under poultry manure fertilization. Treatments consist of 7 cultivars (1 local cultivar inclusive) combined factorially with two poultry manure levels (0 and 6 t/ha). A total of 14 treatments was obtained and laid in a Randomized Complete Block Design (RCBD) with three (3) replications giving a total of 42 plots. Results showed that all cultivars differed significantly (P